FRI0181 THE PLUTO STUDY: INTRAVENOUS BELIMUMAB IN CHILDREN WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (June 2019) - Ruperto, Nicolino; Abud-Mendoza, Carlos; Viola, Diego O.; Calvo, Inmaculada; Levy, Deborah M.; Gallegos, Julia Calderon; Ferrandiz, Manuel; Chasnyk, Vyacheslav; Keltsev, Vladimir; Anton, Jordi; Gastanaga, Maria; Shishov, Michael; et al.
Abstract : Background: Belimumab (BEL), a monoclonal antibody targeting the B-lymphocyte stimulator, is approved in adults with active systemic lupus erythematosus (SLE). This is the first clinical trial of belimumab in pediatric patients with childhood-onset SLE (cSLE). Objectives: PLUTO, a Phase 2, randomised, double-blind trial (BEL114055; NCT01649765 ), evaluated the efficacy, safety and pharmacokinetics (PK) of intravenous (IV) BEL vs placebo (PBO), plus standard of care (SoC), in cSLE. Methods: Patients with cSLE 5–17 years of age were randomised to BEL 10 mg/kg IV or PBO every 4 weeks, plus SoC. Primary endpoint: SRI4 at Week 52. Major secondary endpoints: PRINTO/ACR 30 and 50 cSLE evaluation criteria for improvement at Week 52; cSLE core response variables at Week 52; and sustained SRI4 and ParentGA (patient well-being) responses (Weeks 44–52). Other endpoints: components of SRI4 at Week 52; and frequency of severe flares using the modified SELENA-SLEDAI Flare Index. Safety and PK were assessed. Analyses were performed on the intent-to-treat population. The study was not powered to test for differences between groups; p-values were not calculated. Results: 93 patients were included (BEL, n=53; PBO, n=40). Groups (BEL vs PBO) were balanced at baseline for age (mean [standard deviation] 13.5 [2.59] vs 14.8 [2.17] years, respectively) and SELENA-SLEDAI score (10.3 [3.34] vs 10.4 [3.63], respectively). Compared with PBO, there were more SRI4 responders (including all 3 components of SRI4), and PRINTO/ACR 30 and 50 responders in the BEL group (Figure ). Likewise, more BEL than PBO recipients had sustained improvement of SRI and patient well-being (ParentGA) (Figure ). Changes in cSLE core response variables are shown in the Table . Severe flares were 62% less frequent with BEL vs PBO (hazard ratio 0.38 [95% CI 0.18, 0.82]). PK: BEL exposures in cSLE were similar to adult SLE studies. 9/53 (17%) BEL patients had ≥1 serious adverse event vs 14/40 (35%) PBO patients. One PBO patient died of acute pancreatitis. Conclusion: The benefit:risk profile of BEL IV plus SoC in cSLE is generally consistent with BEL in adult SLE. The 10 mg/kg IV dose used in adults may be an appropriate dose in cSLE. Acknowledgement: The authors would like to acknowledge all investigators (PRINTO, PRCSG and otherwise affiliated) for the PLUTO study. Study funded by GSK. Gosia Carless, PhD, Fishawack Indicia Ltd, UK, provided editorial assistance funded by GSK. Disclosure of Interests: Nicolino Ruperto Grant/research support from: The Gaslini Hospital, where NR works as full-time public employee, has received contributions (> 10.000 USD each) from the following industries in the last 3 years: BMS, Eli-Lilly, GlaxoSmithKline, F Hoffmann-La Roche, Janssen, Novartis, Pfizer, Sobi. This funding has been reinvested for the research activities of the hospital in a fully independent manner, without any commitment with third parties., Consultant for: Received honoraria for consultancies or speaker bureaus (< 10.000 USD each) from the following pharmaceutical companies in the past 3 years: Ablynx, AbbVie, Astrazeneca-Medimmune, Biogen, Boehringer, Bristol-Myers Squibb, Eli-Lilly, EMD Serono, GlaxoSmithKline, Hoffmann-La Roche, Janssen, Merck, Novartis, Pfizer, R-Pharma, SanofiServier, Sinergie, Sobi and Takeda., Speakers bureau: Received honoraria for consultancies or speaker bureaus (< 10.000 USD each) from the following pharmaceutical companies in the past 3 years: Ablynx, AbbVie, Astrazeneca-Medimmune, Biogen, Boehringer, Bristol-Myers Squibb, Eli-Lilly, EMD Serono, GlaxoSmithKline, Hoffmann-La Roche, Janssen, Merck, Novartis, Pfizer, R-Pharma, SanofiServier, Sinergie, Sobi and Takeda., Carlos Abud-Mendoza: None declared, Diego O Viola: None declared, Inmaculada Calvo Grant/research support from: received research grants from Pfizer, Roche, Novartis, Clementia, Sanofi, MSD, BMS and GSK, Consultant for: Advisory boards: Novartis, AbbVie, Speakers bureau: AbbVie, Roche, Novartis, SOBI, Deborah M Levy Consultant for: received consulting fees and/or honoraria from AbbVie and Janssen, Julia Calderon Gallegos: None declared, Manuel Ferrandiz: None declared, Vyacheslav Chasnyk: None declared, Vladimir Keltsev: None declared, Jordi Anton Grant/research support from: JA has received grant/research support, consulting fees and/or honoraria from AbbVie, Alexion, BMS, ChemoCentryx, Gebro, GSK, Novartis, Novimmune, Pfizer, Roche, Sanofi and Sobi, Consultant for: JA has received grant/research support, consulting fees and/or honoraria from AbbVie, Alexion, BMS, ChemoCentryx, Gebro, GSK, Novartis, Novimmune, Pfizer, Roche, Sanofi and Sobi, Maria Gastanaga: None declared, Michael Shishov: None declared, Alina Boteanu: None declared, Michael Henrickson: None declared, Damon Bass Shareholder of: GSK, Employee of: GSK, Ken Clark Shareholder of: GSK, Employee of: GSK, Anne Hammer Shareholder of: GSK, Employee of: GSK, Beulah Ji Shareholder of: GSK, Employee of: GSK, Antonio Nino Shareholder of: GSK, Employee of: GSK, David Roth Shareholder of: GSK, Employee of: GSK, Herbert Struemper Shareholder of: GSK, Employee of: GSK, Mei-Lun Wang Employee of: former employee of GSK, Alberto Martini Consultant for: I do not have any conflict of interest to declare since starting from 1 March 2016 I became the Scientific Director of the G. Gaslini Hospital; therefore, my role does not allow me to render private consultancies resulting in personal income. I perform consultancy activities on behalf of the Gaslini Institute for the companies listed below: AbbVie, Biogen, Boehringer Ingelheim, Bristol-Myers Squibb, EMD Serono, Janssen, Novartis, Pfizer, R-Pharm. The money received for these activities are directly transferred to the Gaslini Institute's bank account. Before March 2016, I was the head of the Pediatric Rheumatology Department at the G. Gaslini Hospital, where the PRINTO Coordinating Centre is located. For the coordination activity of the PRINTO network, the Gaslini Hospital received contributions from the industries listed in this section. This money has been reinvested for the research activities of the hospital in fully independent manners besides any commitment with third parties., Daniel J Lovell Consultant for: Consulting fees and/or honoraria from Astra Zeneca, Wyeth Pharma, Amgen, Abbott, Pfizer, F. Hoffmann-La Roche, Novartis, UBC, Takeda, GSK, Boehringer, and Celgene, Hermine Brunner Grant/research support from: Bristol-Myers Squibb, Pfizer, Consultant for: Pfizer, Bristol-Myers Squibb, Janssen, Novartis, Lilly, Roche, GlaxoSmithKline, Sanofi, Speakers bureau: Novartis, Roche